A parametric study on design and characteristics of stepwise-built functionally graded Hydroxyapatite/Titanium - Siti Nur Sakinah, Jamaludin (2015)
Demand exists to enhance the performance and capability of engineering materials for various advanced engineering applications such as bioengineering, biomedical, aerospace and electronic devices. In order to fulfil the demand, concept of property gradation in functionally graded materials (FGMs) has been introduced and it allows the elimination of many limitations found in conventional materials. As the material selection is the key element of developing an FGM, the composition of hydroxyapatite (HA) as the ceramic phase and titanium (Ti) as the metallic phase in HA/Ti FGM is seen as an excellent combination of high biocompatibility and high thermal resistance with high mechanical properties in a structural domain. However as far as the author is aware, a comprehensive data on various characteristics of the FGM as well as its optimal processing condition is yet been reported thus it becomes the main direction of this study. This thesis reports the development and the results of a combined theoretical and experimental investigation of HA/Ti as FGM under various geometrical design parameters that affect the property gradient and loading conditions. The theoretical model has been developed based on finite element method (FEM) to solve for the stress and the coupled thermal stress equations. Several numerical studies for HA/Ti FGM plate were then carried out using analysis system (ANSYS) software and rule of mixture (ROM) formulations to verify the basis of the present model. It includes the investigation of the parametric effects on the performance of the FGM towards optimizing the geometrical design of a pre-designed cylindrical HA/Ti FGM plate using a 2-D axisymmetric FE Model. The cylindrical shape is selected to minimize sintering issue due to the sharp edge effects. Subsequently, a 3-D FE model is further developed for the parametric study on various responses fields such as displacement and stress components included in the FGM plate under various loading conditions. These models are verified by quantitative agreement achieved between present results and those published in literature. Concurrently, an experimental program was conducted using HA and Ti powders which were prepared via powder metallurgy technique for the measurement of the actual mechanical properties of the FGM. From these parametric studies, it is expected that a lot of numerical and empirical data onthe characteristics corresponding to various loading conditions as well as criteria for designing and preparing the optimum HA/Ti FGM can be provided. In the numerical studies, the optimization analysis is used to quantify the effects of grading parameter, number of layer and thickness on residual stresses distribution of the FGM. The effects of these geometrical parameters are further considered in the parametric study on various behaviours of the FGM under isothermal, thermal and thermo-mechanical loading conditions. The aim of these studies is to reveal that the property gradation profile does influence the material’s performance under various conditions. The results from the optimization analysis concluded the optimum FGM design which can be developed by linearly graded the material composition and providing minimum six number of layer with each having a particular thickness that can preserve the material gradation effectiveness. These criteria were acquired by the minimum residual stresses distribution and higher residual stresses relaxation profiles. The findings from the parametric study revealed that the loading field distribution was another factor that reflects the thermo-elastic properties of the HA/Ti FGM plate and the stress intensity distributions were found as a good indicator to the spot of failures initiation on the FGM structure. The HA/Ti FGM plate is found to be able to withstand the thermal stresses while preserving the high toughness properties and thus shows its ability to operate at high temperature. Due to the limited available facilities, the fabrication of the HA/TiFGM via cold compaction and pressure-less sintering techniques does not guarantee good findings. The densification and grain boundary energy minimization of the powdered compacts during sintering stage was found as the most challenging part in the fabrication which still not completely understood from the experimental studies. The varied operating parameters considered so far are not appropriate to produce sufficient driving force for the sintering of the FGM sample. The metallurgical characteristics and microstructural topology characterized via scanning electron microscope (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) reveal the sensitivity of HA and Ti material to the sintering conditions as well as impurities presence during heat treatment process. The variation of density and hardness along the gradient plane of the FGM were measured using water immersion and Vicker’s micro-hardness tester respectively but the results cannot represent the high performance criteria. The empirical evidences showing the undeniable limitations of cold processing technique highlighted from the experimental works represents the basis of HA/Ti FGM processing via powder metallurgy (PM) approach. This could be a proper guideline for the improvement of the FGM fabrication via particulate processing which is cost effectiveness in future. The capability of hot processing technique on enhancing the sintering behaviour of the FGM will be a great topic to be explored towards determining the optimal processing conditions of the considered material